Evaluation of prognostic significance of lymphovascular space invasion in early stage endometrial cancer: a systematic review and meta-analysis - Qin, Zhao-juan; Wang, Yi-si; Chen, Ya-li; Zheng, Ai; Han, Ling (Frontiers in Oncology, 2024)
Background Studies evaluating the prognostic significance of lymphovascular space invasion (LVSI) in early stage endometrial cancer (EC) are conflicting. Objectives To evaluate whether LVSI identified in stage I EC is associated with worse survival. Search strategy A comprehensive literature search of three databases (Embase, PubMed, and Cochrane) was performed up to April 30th 2023. Selection criteria Cohort studies that have evaluated the relationship between LVSI and prognosis in patients with stage I EC were included. Data collection and analysis Two authors independently assessed the studies for inclusion, extracted the data of recurrence and survival, and conducted meta-analysis using random effects model. Heterogeneity was evaluated by I2 test. Main results A total of 15 studies involving 6,705 patients were included in the meta-analysis. The overall pooled rate of LVSI was 14% [95% confidence interval (CI) CI 0.09-0.18] in stage I EC. LVSI was significantly associated with a higher risk of recurrence [odds ratio (OR) = 2.79, 95%CI 2.07-3.77], reduced overall survival (OS) [hazard ratio (HR)=5.19, 95%CI 3.33-8.07] and recurrence free survival (RFS) [HR = 5.26, 95%CI 3.45-8.02] in stage I EC patients. Similarly, LVSI was associated with an increased risk of recurrence [OR= 3.10, 95%CI 2.13-4.51], decreased OS [HR=5.52, 95%CI 2.16-14.09] and RFS [HR = 4.81, 95%CI 2.34-9.91] in stage IA grade 1 or 2 endometrioid carcinoma patients. Conclusion The presence of LVSI in stage I EC and in stage IA, grade 1 or 2 endometrioid carcinoma is associated with an increased risk of recurrence, lower OS and RFS. Systematic Review Registration https://www.crd.york.ac.uk/prospero/, identifier 42023425231.